Les épicènes : une notion caméléonesque - Daniel Elmiger (Glad!)
Today, nouns, adjectives, pronouns, etc. that have a single form and are used indiscriminately in the masculine and feminine gender are most often considered epicene. In the grammatical tradition, however, we also find another usage: initially, nouns that had one gender but were used for animals or humans regardless of their sex or gender identity (e.g., in French le crabe, la perdrix, l’individu ou la personne) were considered epicene. More generally, epicene has also long been taken to mean any form of non-discriminatory language use: epicene was (and still is) therefore in competition with inclusive.